Leaf and canopy photosynthesis of a chlorophyll deficient soybean mutant. (20th April 2018) - Sakowska, Karolina; Alberti, Giorgio; Genesio, Lorenzo; Peressotti, Alessandro; Delle Vedove, Gemini; Gianelle, Damiano; Colombo, Roberto; Rodeghiero, Mirco; Panigada, Cinzia; Juszczak, Radosław; Celesti, Marco; Rossini, Micol; et al.
Abstract: The photosynthetic, optical, and morphological characteristics of a chlorophyll‐deficient (Chl‐deficient) "yellow" soybean mutant (MinnGold) were examined in comparison with 2 green varieties (MN0095 and Eiko). Despite the large difference in Chl content, similar leaf photosynthesis rates were maintained in the Chl‐deficient mutant by offsetting the reduced absorption of red photons by a small increase in photochemical efficiency and lower non‐photochemical quenching. When grown in the field, at full canopy cover, the mutants reflected a significantly larger proportion of incoming shortwave radiation, but the total canopy light absorption was only slightly reduced, most likely due to a deeper penetration of light into the canopy space. As a consequence, canopy‐scale gross primary production and ecosystem respiration were comparable between the Chl‐deficient mutant and the green variety. However, total biomass production was lower in the mutant, which indicates that processes other than steady state photosynthesis caused a reduction in biomass accumulation over time. Analysis of non‐photochemical quenching relaxation and gas exchange in Chl‐deficient and green leaves after transitions from high to low light conditions suggested that dynamic photosynthesis might be responsible for the reduced biomass production in the Chl‐deficient mutant under field conditions. Abstract : The introduction of crop varieties with high canopy albedo has been proposed as a Shortway Radiation Management scheme to mitigate global warming, even if large uncertainties remain on their potential productivity. In this study, the photosynthetic, optical, and biophysical properties of a chlorophyll‐deficient (Chl‐deficient) soybean mutant characterized by a high albedo were analysed in comparison with 2 green soybean accessions. We show that, in steady state conditions, photosynthetic rates of Chl‐deficient and green varieties were almost the same, but biomass production in the field was reduced in the Chl‐deficient mutant. Dynamic photosynthesis is likely to be responsible for such a difference.